Sewa Pacar Sebagai Bentuk Aktualisasi Diri Pada Tokoh Kinoshita Kazuya Dalam Video Channel YouTube Muse Indonesia Berjudul “Pacar Sewaan” Episode 2 - Ariyanto, Nazla Iftinan; Santoso, Budi (Vocational College of Diponegoro University, 2024)
This research aims to analyze how Kinoshita Kazuya's character tries to fulfill his self-actualization needs through rent a girlfriend. The author uses a qualitative descriptive research method. This research design uses literary psychology, specifically the hierarchy of needs from Abraham Maslow. With a humanistic approach that uses Maslow's five levels of needs, including physiological needs, safety needs, social needs, esteem needs, and self-actualization needs from Muse Indonesia's YouTube channel video entitled